eMarketing The Essential Guide to Marketing in a Digital World - Solomons, Dionne; Kliphuis, Tania; Wadley, Michelle (Open textbook library., 2022)
Since our 10th Anniversary Edition of eMarketing: The Essential Guide to Marketing in a Digital World, we have witnessed a global wave of change that has had an undeniable impact on how we live, connect, and communicate worldwide. There is no doubt that the COVID-19 pandemic has, and will continue to have, a lasting effect on human reality. With this in mind, we are incredibly proud to present the 7th Edition of our textbook.